Histopathological changes in the placenta of women with COVID-19 infection: A review article - Ghazi, Hameda Abd Al-Mahdi; Burhan, Mariam Mohammed; Mekkey, Shereen M.; Kazem, Hadeer Waleed (Jour Med Resh and Health Sci, 2022)
Background: The systemic nature of SARS-CoV-2 and the involvement of various organs by pathological changes have been reported by a lot of authors recently. The placenta plays a major role in providing the growing embryo with nutrients and oxygen in addition to its efficient role in protecting against toxins and infectious agents. However, viral transmission from mother to fetus has been documented. Aim of the study: In the current review we were aiming at summarizing the main histopathological changes seen in placental tissues of women with COVID-19. Results: Several authors documented histopathological changes in the placental tissues either in all cases examined or in some cases. These changes mainly involved chronic villi and their supporting structures and their vasculature. Necrosis, edema, thrombosis, vascular obliterations and inflammatory cell infiltrates were the main histopathological changes in various reports and various proportions. Some authors denied the specific nature of these changes while others blamed COVID-19 to be the causative agent of these changes. Conclusion: The main histopathological changes reported in the placentas of pregnant women with SARS-CoV-2 infection can be summarized as follows: Chorangiosis, thrombus formation in the subchorionic spaces and the intervillous spaces, villous agglutination, debris accumulation in the intervillous space, trophoblast necrosis, focal avascular villi, decidual arteriopathy, accelerated villous maturation, fibrinoid necrosis, retroplacental hematoma, edematous villi, lymphocytic infiltration and macrophage infiltration of the deciduas, fibrotic villi, syncytial knots, microcalcifications, karyorrhexis in stromal cells, acute funisitis and acute chorioamnionitis; however, some opinions favor non-specificity of these findings.